Labor reform and dignified work: a possible combination? - Rafagnin, Maritânia Salete Salvi; Nogueira, Vera Maria Ribeiro (Argumentum, 2021)
This article compares some aspects of the 2017 Labor Reform with the concept of decent work. It starts from the statement made by the federal government and disseminated by the media and economic elites regarding the relevance of the reform for the integration of Brazil into the reproductive dynamics of capital in the 21st century. Through documentary research, articles 223-G; 611-A; 611-B; 582 and 507-B of Law no. 13,467/2017 are analyzed, as well as the unrestricted outsourcing contained in Law no. 13,429/2017, juxtaposing these devices with the concept of dignified work. The results point to the incompatibility of the rules with this concept. In conclusion, it is evident that the deregulation and flexibilisation within the analyzed articles form a process of the dismantling the labor rights established by the neoliberal model, implying new morphologies in labor precariousness.